“Activate your Wait” project : pilot study carried out at a thermal centre - Pasquarella, Cesira; Bizzarro, Assunta; Martini, Rosamaria; Ricci, Bernardino; Martini, Raffaella; Colucci, Maria Eugenia; Rossi, Deanna; Faetani, Lorenzo; Ghizzoni, Daniele; Tamarri, Federica; Seidenari, Chiara; Saccani, Elisa; et al. (Acta Biomedica Atenei Parmensis, 2020)
Physical activity is recognised as a major health determinant, with positive effects on health, environmentalsustainability and economy. National surveillance data show that one out of three Italians - adultand elderly alike - declares to be sedentary, with a progressively increasing trend. From the urgent need toimplement strategies to promote physical activity the “Activate your Wait” (“Attiva l’Attesa”) project wasborn, aimed at transforming the waiting pauses during day to day life into opportunities to perform simplestretching and active mobilization exercises. The pilot study was carried out at the Terme S. Egidio, SuioTerme Castelforte (Latina). The results of the questionnaire distributed in the pre-intervention phase, aimedat assessing the users’ interest in the project and physical activity in general, are reported. The questionnairewas administrated in the waiting rooms in September 2018 and September 2019. A total of 129 subjectsresponded to the questionnaire: 43% declared themselves sedentary, 73% reported willingness to performsimple physical exercises while waiting, and 76% believed that physical activity during waiting moments couldhave a positive impact on health. The project’s subsequent goal is to identify suitable exercises to be proposedduring the intervention period, which can be easily reproduced independently by users in their everyday life.